The peroneus brevis tendon at its insertion site on fifth metatarsal bone. Issue 1 (March 2016) - Imre, Nurcan; Kocabiyik, Necdet; Sanal, H. Tuba; Uysal, Murat; Ozan, Hasan; Yazar, Fatih
Abstract: Background: The differences at the attachment site of peroneus brevis (PB) to the fifth metatarsal bone is important in terms of the forces exerted on the bone and hence the mechanism of fractures involving this structure. In this study, we investigated the anatomical properties of PB at the insertion site to the base of fifth metatarsal bone, its possible intertendinous connections with peroneus tertius (PT) and their possible effects on the fracture occurrence at the bony attachment site. Methods: The length and the width of PB tendons at their mid- and end-points were measured and classified according to the insertion types. Besides, the length and the width of the base of fifth metatarsal bone were assessed. The slips extending from the PB tendons and their relationship with PT were also evaluated. The data was compared statistically with each other and between the right and left sides. Results: The length of PB tendon was measured 79.57 ± 15.40 mm on the right side; 81.48 ± 14.31 mm on the left. The width of PB tendon at the mid-point was 4.46 ± 0.80 mm on the right side; 4.42 ± 0.94 mm on the left. The width of the tendon at its insertion point was measured 14.85 ± 3.40 mm and 15.16 ± 3.42 mm on the right and left sides respectively. PB was divided into three types according to its attachment to base of fifth metatarsal bone (5thMB). Type I, Type II and Type III were observed at the rates of 59.5%, 28.6% and 11.5% respectively. It was observed that the slips to the bone were extending more commonly from PB than from PT and that the large majority of them were single having their insertions on the base of the proximal phalanx of the fifth toe. Conclusions: Knowing the width and insertional types of PB aids in understanding the mechanism of fractures at the site of bony attachment. The existence of slips may help the surgeon in the procedures involving PB or the lateral side of the forefoot.